2016
DOI: 10.1002/biof.1319
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with linoleic acid‐rich soybean oil stimulates macrophage foam cell formation via increased oxidative stress and diacylglycerol acyltransferase1‐mediated triglyceride biosynthesis

Abstract: During the last decades there has been a staggering rise in human consumption of soybean oil (SO) and its major polyunsaturated fatty acid linoleic acid (LA). The role of SO or LA in cardiovascular diseases is highly controversial, and their impact on macrophage foam cell formation, the hallmark of early atherogenesis, is unclear. To investigate the effects of high SO or LA intake on macrophage lipid metabolism and the related mechanisms of action, C57BL/6 mice were orally supplemented with increasing levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Among them, samples 14 and 15 (both of Brazilian origin) were distinctive in composition compared to the other omega-3 supplements since they presented low levels of EPA and DHA, and high levels of linoleic acid (LA, 18:2n-6). Thus, since soybean oil has in its composition mainly LA, 22 the same fatty acids were quantified in this vegetable oil in order to compare their contents with those found in samples 14 and 15; and the results are presented in Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Among them, samples 14 and 15 (both of Brazilian origin) were distinctive in composition compared to the other omega-3 supplements since they presented low levels of EPA and DHA, and high levels of linoleic acid (LA, 18:2n-6). Thus, since soybean oil has in its composition mainly LA, 22 the same fatty acids were quantified in this vegetable oil in order to compare their contents with those found in samples 14 and 15; and the results are presented in Table 2.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Collectively these data indicate that 20-HETE is capable of modulating endogenously expressed TRPC6 channels of podocytes. We have previously shown that currents with similar properties are activated by exposing podocytes to a membrane-permeable diacylglycerol analog (OAG) (Anderson et al, 2013; Kim et al, 2013). Here we observed that 100 μM OAG evoked an additional increase in currents in podocytes after prior activation of TRPC6 by 20 μM 20-HETE.…”
Section: Resultsmentioning
confidence: 99%
“…Podocyte differentiation and expression of podocyte markers were induced by removal of γ-interferon and raising temperature to 37°C for 14 days. TRPC6 siRNA, podocin siRNA and non-targeting control siRNA were transfected into differentiated MPC-5 cells after isolation using Lipofectamine 3000™ (Invitrogen) in serum-reduced medium according to the manufacturer's directions (Anderson et al, 2013). Electrophysiological and biochemical analyses were carried out 24 h after transfection with siRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations